1984
DOI: 10.1007/bf00442743
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for urinary calcium excretion and screening for hypercalciuria in children and adolescents

Abstract: Hypercalciuria is of continuing interest as one of the risk factors for stone disease in children, but the definition, incidence and pathogenesis are controversial. Therefore reference values for the urinary calcium/creatinine (Ca/Cr) ratios were established in 564 healthy children aged 6-17.9 years during the fasting state (09.00 h) and in 236 of them also in the post-absorptive state about 2 h after lunch (14.00-16.00 h). The Ca/Cr ratios in both urine specimens were independent of age and sex, rendering it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
1
12

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(69 citation statements)
references
References 38 publications
7
49
1
12
Order By: Relevance
“…As for most analytes, the lower and upper reference limits are assumed to demarcate the estimated 2.5 th and 97.5 th percentiles respectively, of the underlying distribution of values [24], percentile values of urinary Ca/Cr ratio were calculated. 95 th and 97.5 th percentile for urinary Ca/Cr ratio of different age groups in present study in this geographic area was the same as some reports and different with other [1,6,9,10,[14][15][18][19][20][21][22][23][25][26][27][28][29]. Then upper reference value of urinary Ca/Cr ratio of different age group were found and this to some extent different from one previous study [11].…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…As for most analytes, the lower and upper reference limits are assumed to demarcate the estimated 2.5 th and 97.5 th percentiles respectively, of the underlying distribution of values [24], percentile values of urinary Ca/Cr ratio were calculated. 95 th and 97.5 th percentile for urinary Ca/Cr ratio of different age groups in present study in this geographic area was the same as some reports and different with other [1,6,9,10,[14][15][18][19][20][21][22][23][25][26][27][28][29]. Then upper reference value of urinary Ca/Cr ratio of different age group were found and this to some extent different from one previous study [11].…”
Section: Resultssupporting
confidence: 60%
“…The prevalence of idiopathic hypercalciuria (IH) has been reported to vary between 2.9% -6.2% in the age group of 3 months to 18 years [1][2][3][4][5][6]. The majority of these cases are asymptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26]29 Similarly, while many studies show no relationship between the gender and UCa/UCr ratio, there are also different studies demonstrating that IHC is more common in girls in some of them, and in boys in some others. 20,22,24,29,33,34 In our study, there was a weak negative but statistically significant correlation between the urinary calcium excretion and age. However, no significant difference between the boys and girls was found in the prevalence of IHC although the mean UCa/UCr ratios were significantly higher in boys.…”
Section: Discussionmentioning
confidence: 45%
“…This can be attributed to the difference between the children in terms of race, geographic area, and particularly eating habits. [22][23][24][25][26][27] In a study performed by So et al 28 with 368 children, the mean UCa/UCr ratio was found as 0.10 in children aged between 19 months and 6 years, and 0.09 in children aged !7 years. In another study conducted by Moore et al, 29 the mean UCa/UCr ratio was found as 0.06 AE 0.062 where the majority of the subjects were black children.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, 51Cr_ EDTA clearance was done before OLT. Urinary glucose excretion <2 g/24 h, urinary calcium/ creatinine ratio <0.22 mg/mg (=0.63 mmollmmol) and urinary a-amino nitrogen excretion ::sO.20 mmol/kg body weight/24 h (::SO.30 in patients under 1 y of age) were considered normal (18). Phosphaturia was defined as TmP/GFR more than 2 SD below age-corrected mean (19).…”
Section: Methodsmentioning
confidence: 99%